Synthesis of 1,2,4-trihalophenothiazin-3-ones and Their Conversion into (1,4)-Benzothiazino-(2,3-b)-Phenothiazines - Ojha, K.G.; Mathur, Neha; Kawadiya, Mahveer; Tanwar, M. (Asian Journal of Chemistry, 2010)
1,2,4-Trihalophenothiazin-3-ones were prepared by condensing 2-amino benzenthiols with chloranil/bromanil in 1 : 1 molar ratio. Compounds were further condensed with the same or different 2-aminobenzenthiol which afforded (1,4 )-benzothiazino-(2,3-b )-phenothiazines.